Foreign Direct Investment And Manufacturing Growth Nexus : Evidence From ASEAN - 4 Countries - Marwan, Hj. Hashim @ Hassim (2001)

(untitled)
This study is an attempt to provide some further insight on the relationship between manufacturing sector growth and foreign direct investment in four ASEAN countries viz. Malaysia, Thailand, Indonesia and the Philippines. This study is based on the secondary data obtained from Asian Development Bank official publications from the year 1982 to 1999. The purpose of the study is to specify and estimate a structural model for manufacturing growth and foreign direct investment. The structural model consists of two equations, one for manufacturing sector growth and the other foreign direct investment. Two stage feast squares method is used to estimate the model. The results of this study are not consistent with most of the previous studies. Except for the Philippines and Malaysia, the results for Thailand and Indonesia do not indicate any significant relationship between foreign direct investment and manufacturing sector growth. For Indonesia, the model failed to describe the nature of the relationship between all the tested variables.